Study of Structure Transition and Crystallization of Amorphous Silica under Compression - Thuy Trang, Giap Thi; Kien, Pham Huu (VNU Journal of Science: Mathematics - Physics, 2020)
In this work, we use molecular dynamic (MD) simulation to study of the structure transition and crystallization of amorphous silica (SiO 2 ) under compression. The structural evolution of amorphous SiO 2 is explained through radial distribution function, coordination number distribution, bond angle distribution and visualization. Simulation result shown that there is a structural transformation from tetrahedral to octahedral network through SiO 5 units. In the 5-15 GPa pressure range, structural transformation occurs powerfully and there are three structural phases corresponding to SiO 4 -, SiO 5 -, and SiO 6 - ones. At 15 GPa, octahedral-network (SiO 6 ) is dominant. It is the first time we showed that when pressure is higher than 20 GPa, octahedral-network of amorphous SiO 2 has a tendency to transform to stishovite crystalline phase.